Joyce, Dante, and the poetics of literary relations : language and meaning in Finnegans wake - Boldrini, Lucia (Cambridge University Press, 2001)
Boldrini's study examines how the literary and linguistic theories of Dante's Divine Comedy helped shape the radical narrative techniques of Joyce's last novel Finnegans Wake. This book will appeal to scholars and students interested in Joyce, Dante, and questions of literary relations.